2016
DOI: 10.1007/s40259-016-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologists’ Perceptions of Biosimilar Medicines Prescription: Findings from a French Web-Based Survey

Abstract: Our survey gave a better appreciation of the concerns associated with biosimilar prescriptions. Targeted communication initiatives, deeper experience and availability of new clinical data may help to address the outstanding questions and should overcome the misunderstandings surrounding biosimilar drugs among rheumatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 26 publications
1
49
1
Order By: Relevance
“…Twenty surveys met the inclusion criteria and were included in this systematic review ( Figure 1). The included studies originated from the United States of America [15][16][17] , Belgium 18,19 , France [20][21][22] , Germany 23,24 , Italy 25 , Ireland 26 , Malta 27 , Hungary 28 , and the United Kingdom (UK) 29 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty surveys met the inclusion criteria and were included in this systematic review ( Figure 1). The included studies originated from the United States of America [15][16][17] , Belgium 18,19 , France [20][21][22] , Germany 23,24 , Italy 25 , Ireland 26 , Malta 27 , Hungary 28 , and the United Kingdom (UK) 29 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies quantified clinicians' biosimilar prescribing habits. 15,17,[29][30][31][32][33][34]19,[21][22][23][24][25][26]28 In Danese et al 30 (EU, 2014), 61% of gastroenterologists felt little or no confidence in using biosimilars, 26% felt confident enough, 8% felt very confident, and 5% felt totally confident. When the survey was repeated one year after biosimilars became available in the EU, confidence had increased, as 19.5% of gastroenterologists felt little or no confidence in using biosimilars, 33.9% felt confident enough, 17.8% felt very confident, and 28.8% felt totally confident (EU, 2016).…”
Section: Biosimilar Prescribing Behaviorsmentioning
confidence: 99%
“…A recent survey among U.S.‐based specialty physicians who already prescribe biologics revealed that, although the majority of respondents had heard of biosimilars, in‐depth knowledge of fundamental concepts such as the “totality of the evidence” was low . Other physician surveys have revealed general positivity toward biosimilars but uncertainty regarding issues such as extrapolation . Similar knowledge gaps are likely among pharmacists, nurses, and other health care practitioners .…”
Section: Health Care Professional and Patient Perceptions: Trust And mentioning
confidence: 99%
“…Although the uptake of biosimilars has increased considerably over recent years [3][4][5], some physicians have expressed concerns about the manufacturing process and quality [4]. Such concerns may be partly fuelled by reports of the potential for variability in the manufacturing process which might lead to divergence or 'drift' between biosimilars and the reference product.…”
Section: Introductionmentioning
confidence: 99%